2013
DOI: 10.1590/0004-282x20130098
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis in South America: month of birth in different latitudes does not seem to interfere with the prevalence or progression of the disease

Abstract: Objective To assess whether the month of birth in different latitudes of South America might influence the presence or severity of multiple sclerosis (MS) later in life. Methods Neurologists in four South American countries working at MS units collected data on their patients' month of birth, gender, age, and disease progression. Results Analysis of data from 1207 MS patients and 1207 control subjects did not show any significant variation in the month of birth regarding the prevalence of MS in four latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Study of different latitudes of South America showed significant variation. Patients born to mothers who were pregnant at different Southern latitudes do not follow the seasonal pattern observed at high Northern latitudes (12). Regarding the MOB and risk of MS, vitamin D, as a promoter of some alleles, also promotes Th2 function and inhibit the proinflammatory cytokines, IL-1a, IL-2β, and TNFα (13).…”
Section: Introductionmentioning
confidence: 99%
“…Study of different latitudes of South America showed significant variation. Patients born to mothers who were pregnant at different Southern latitudes do not follow the seasonal pattern observed at high Northern latitudes (12). Regarding the MOB and risk of MS, vitamin D, as a promoter of some alleles, also promotes Th2 function and inhibit the proinflammatory cytokines, IL-1a, IL-2β, and TNFα (13).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic disease in which patient independence requires training in self-care and self-management [1]. About 2.5 million people around the world [2], and 5-30 individuals per 100,000 people in Iran suffer from MS [3]. The prevalence of the disease is unfortunately on the rise in Iran and the number of MS cases recorded in different medical centers of the country have increased by three-four times over the past several years [4].…”
Section: Introductionmentioning
confidence: 99%
“…There are about 2.5 million people with MS worldwide (2). The prevalence of MS is reported as 5 -30 per 100,000 people in Iran (3).…”
Section: Introductionmentioning
confidence: 99%